Polycaprolactone nanofibres loaded with 20(S)-protopanaxadiol for in vitro and in vivo anti-tumour activity study. Issue 5 (2nd May 2018) - Liu, Dan-qing; Cheng, Zhi-qiang; Feng, Qing-jie; Li, He-jie; Ye, Shu-feng; Teng, Bo
Abstract : In this work, 20( S )-protopanaxadiol (PPD)-loaded polycaprolactone (PCL) nanofibres were successfully fabricated by the electrospinning technique using Tween 80 as a solubilizer. Firstly, smooth and continuous nanofibres were collected using suitable solvents and appropriate spinning conditions. Secondly, nanofibre mats were characterized by scanning electron microscopy, thermogravimetric (TG) analysis, Fourier transform infrared spectroscopy and mechanical testing. Finally, nanofibrous membranes were evaluated using water contact angle, in vitro drug release, biodegradation test, in vitro and in vivo anti-tumour activity and cell apoptosis assay. Scanning electron microscopic observations indicated that the diameter of the drug-loaded nanofibres increased with the increase of drug concentration. TG analysis and mechanical test showed that nanofibres were equipped with great thermal and mechanical properties. Biodegradation test exhibited that the structure of fabricated nanofibres had a certain degree of change after 15 days. An in vitro release study showed that PPD from drug-loaded nanofibres could be released in a sustained and prolonged mode. The cytotoxic effect of drug-loaded nanofibre mats examined on human laryngeal carcinoma cells (Hep-2 cells) demonstrated that the prepared nanofibres had a remarkable anti-tumour effect. Meanwhile, the drug-loaded fibre mats showed a super anti-tumour effect in an in vivo anti-tumour study. All in all, PCL nanofibres could be a potential carrier of PPD for cancer treatment.